Kualitas Koliform, Fe, Ph pada Air Baku dan Air Minum Depot di Kota Kendari Tahun 2018 - Nurhayati, Dedeh; Jayadipraja, Erwin Azizi; Harun, Abdul Azis (Sekolah Tinggi Ilmu Kesehatan Karya Kesehatan, 2018)
The existence of Drinking Water Depots (DAM) continues to increase in line with the dynamics of the community's need for quality and safe drinking water for consumption. Drinking water must meet physical, chemical and microbiological requirements. This study aims to determine the quality of Coliform, Fe, pH in Raw Water and Depot Drinking Water in Kendari City. This research is an observational study with a cross sectional study design and was carried out in June - July 2018 in Kendari City. The population in this study were all registered drinking water depots in Kendari City for the January 2018 period, namely 87 depots and a sample of 36 depots with a proportional random sampling technique. Data were obtained using questionnaires and descriptive analysis. The results obtained from 36 depots, the quality of Coliform in Raw Water was mostly 80.6% did not meet the requirements and the quality of Coliform Drinking Water Depot 88.9% met the requirements. Most of the Fe quality in Raw Water, namely 58.3%, met the requirements and the Fe quality in Depot Drinking Water was mostly 86.1%, and the pH quality in Raw Water and drinking water was 100% qualified. The conclusion in this study is that the quality of coliform in raw water is mostly not eligible and most of the drinking water meets the requirements. The quality of Fe in raw water and drinking water mostly meets the requirements and the quality of pH in raw water and drinking water 100% meets health requirements. Suggestions in this study are for the Kendari City Health Office to be able to establish policies in an effort to improve the quality of drinking water depots, especially the quality of microbiology. For the owner of the depot, in order to improve the hygiene and sanitation of the depot so as to minimize the coliform content in the drinking water of the depot